PENCEMARAN MINYAK DI PERAIRAN UTARA PULAU BAWEAN - Sarah Nur Qowiyah; Mahmiah; Rudi Siap Bintoro (Universitas Hang Tuah, 2021)
Marine pollution results in a decrease in the quality and quantity of coastal and marine resources. Most of the people in tambak sub-district have a livelihood as fishermen and work in the field of fish processing industry and seafood trade and the location of the waters are often passed by industrial vessels. This resulted in increased ship activity in the waters of Labuhan Beach, Tambak District, Tanjungori Village. As the activity increases it causes marine pollution. One of the sources of pollution produced is oil spills from former fuel boats or ships that cross the area of the water. This method can provide information about the condition of the waters according to their designation. The purpose of this study is to know the water quality based on the parameters of temperature, pH, salinity and brightness and know how much oil content in the waters of Labuhan Beach, Bawean Island. Sea water sampling was conducted at 4 stations, then the results were compared with sea water quality standards for biota based on KEPMEN LH No.51 Year 2004. The results showed that the oil content ranged from 0.0016%–0.0377%. As for the pH parameter, salinity and brightness in accordance with the quality standard, for the temperature parameter exceeds the standard value of quality. Based on this study, pollution index calculations show that the waters of Labuhan Beach, Bawean Island are in the category of lightly polluted.